Diffuse Loss of Vertebral Body Height and Marrow Changes in a 4-Year-Old with Acute Lymphoblastic Leukemia - Hostmeyer, Sean; Massak, Mark; Cauley, Keith A. (Journal of Pediatric Neurology, 2019)
Acute leukemia can present with a wide range of symptoms and with no classic osseous findings on radiographs. Recognizing subtle imaging abnormalities and raising the possibility of a lymphoproliferative or hematologic pathology may facilitate early diagnosis. Described here is a case of a 4-year-old with back pain that was found to have acute lymphoblastic leukemia with diffuse loss of vertebral body height on plain film radiographs, and with prominent discs, and diffusely abnormal marrow signal on magnetic resonance imaging.
Keywords: acute lymphoblastic leukemia; vertebral body height loss; pediatric bone marrow signal abnormalities